Inverser la classe : effets sur la formation de futurs enseignants - Isabelle Nizet; Florian Meyer
As part of a university teacher training program in secondary education, a flipped classroom design was tested in a course on assessment of learning. Structured in a rather traditional way, class time was, in this course, mainly devoted to conceptual learning while practical learning were done outside of the classroom. From the hypothesis that active pedagogy and differentiation would be appropriate to support the procedural learning targeted in this course, we decided to integrate online self-learning clips about the concepts, in order to further support students procedural learning in the classroom. The initial teaching and learning context has been « hybridized » with the introduction of self-learning materials available remotely asynchronously. The problematization of the situation and the analysis of the experiment carried out are part of the Scholarship of Teaching and Learning approach (SoTL) and the sharing of expertise required for the development of this new training approach is based on the Technological Pedagogical and Content Knowledge (TPACK) model. In order to benefit from this experiment to enrich our teaching, and considering the need to gather scientifically valid evidence for the sustainability of a training approach such as « flipped classroom », our pedagogical engineering was accompanied by a research approach that aimed to describe the appropriation of the resources by students and to characterize the learning dynamics in class from the trainer's point of view.